The evaluation of the educational webinar program of the learning community of guru penggerak through CIPP model - Saputra, Febry Elbi; Mutamin, Nurul; Oktaviani, Wiltri; Hasanah, Ulfah Yuziya; Susanti, Dessi (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to evaluate the educational webinar program by the learning community of Guru Penggerak in Mukomuko Regency. This quantitative research used CIPP evaluation model study by Stufflebeam with a survey approach. In collecting the data, this research used a questionnaire with descriptive statistical analysis distributed through Google Forms to webinar participants. The findings indicated tha: (1) the context aspect indicates that the webinar program can meet the needs of teachers on webinar themes that are relevant to current educational issues and are easy to implement; (2) the input aspect indicates that the organizer of the educational webinar can present competent sources, material, and adequate facilities to the participants; (3) the process aspect indicates that the webinar implementation flow has been in line with the overall plan; and (4) the product aspect indicates that there is a significant improvement in the participants' understanding after attending the webinar. Overall, the contextual aspects indicated that the webinar program was necessary. The themes discussed in the webinars were relevant to current educational issues and had prospects to be applied in teacher learning practices.